2016
DOI: 10.1111/btp.12352
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tree species diversity on a community of weaver spiders in a tropical forest plantation

Abstract: The effects of producer diversity on predators have received little attention in arboreal plant communities, particularly in the tropics. This is particularly true in the case of tree diversity effects on web‐building spiders, one of the most important groups of invertebrate predators in terrestrial plant communities. We evaluated the effects of tree species diversity on the community of weaver spiders associated with big‐leaf mahogany (Swietenia macrophylla) in 19, 21 × 21‐m plots (64 plants/plot) of a tropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 54 publications
3
13
0
Order By: Relevance
“…A very similar pattern was found in a temperate tree diversity experiment [37], concurring with the strong tree species-specific patterns for spider abundance reported earlier [33]. In contrast, species richness and abundance of web-building spiders on mahogany (Swietenia macrophylla) was higher in mixtures of tropical tree plantations than in mahogany monocultures [44].…”
Section: Spiderssupporting
confidence: 86%
“…A very similar pattern was found in a temperate tree diversity experiment [37], concurring with the strong tree species-specific patterns for spider abundance reported earlier [33]. In contrast, species richness and abundance of web-building spiders on mahogany (Swietenia macrophylla) was higher in mixtures of tropical tree plantations than in mahogany monocultures [44].…”
Section: Spiderssupporting
confidence: 86%
“…Host specificity among herbivores arises from interspecific differences in tree morphology, physiology, and phenology, with adaptations to these becoming increasingly host species-specific over time 10 , 26 . From the assemblage composition analyses, and similar to previous work 27 , we suggest that arthropod specialization towards different tree species does not seem to be restricted only to folivores, but might also shift beyond lower trophic levels to include predatory arthropods 28 . Also, the assemblages of herbivores and predators, along with the ants, but not detritivores or tourists, were strongly explained by host same-species cover (the canopy cover of tree species similar to focal tree species within a plot).…”
Section: Discussionsupporting
confidence: 85%
“…volatile organic compounds, induced defences, Zakir et al., ) or other processes independent of leaf traits (e.g. top–down control by predators, Esquivel‐Gómez, Abdala‐Roberts, Pinkus‐Rendón, & Parra‐Tabla, ; Moreira, Mooney, et al., ; Muiruri, Rainio, & Koricheva, ) could account for the effect of neighbour diversity and identity on insect herbivory. This is in accordance with the results of a previous study using the same experimental design but focusing on oak ( Q. robur , Castagneyrol et al., ) which showed that despite clear effects of tree neighbours on leaf traits, traits poorly explained variation in leaf insect herbivory (Castagneyrol et al., ).…”
Section: Discussionmentioning
confidence: 99%